A Rare Cause of Acute Abdomen in Adults: Intestinal Malrotation - Mürşit Dinçer (Haseki Tıp Bülteni, 2017)
Intestinal malrotation is a congenital anomaly of the midgut. The incidence of intestinal malrotation is 1 in 500 live births. It is rarely seen in adults. Most of the symptomatic patients present with acute bowel obstruction, intestinal ischemia or chronic vague abdominal pain. We present a 49-year-old male presenting with the findings of acute intestinal obstruction.